Chinese Initial Teaching Scheme Designed for Indonesian Beginners - Haryono Candra; Yusup Gumilar Sukma (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
As a part of the primary stage of Chinese phonetic teaching, the importance of Chinese initial teaching is self-evident, as initial pronunciation errors can affect the results of communication. Therefore, when Indonesian students begin to learn Chinese phonetics, they should first master the pronunciation characteristics of Chinese initials. This study has made a deeper exploration based on previous studies. This study aims to propose an initial teaching scheme for Indonesian beginners built on sorting out. Through comparison between the consonant systems in Chinese and Indonesian languages, analysis of the difficulties of Indonesian students' acquisition of Chinese initials, and investigation of the arrangement of initials in the â€œScheme of the Chinese Phonetic Alphabetâ€, this study has designed a Chinese initial teaching scheme for Indonesian Chinese beginners with the purpose of improving the quality of Chinese initial teaching in Indonesia. Literature integration analysis and a qualitative research method were adopted in this study. By integrating existing literature and combining them with the authorsâ€™ own research findings, the design of the initial teaching scheme is optimized. The design features of this scheme are mainly reflected in the following aspects: first, arranging Chinese initials from easy to difficult to learn; second, strengthening the teaching and practice of Chinese initials which are different from Indonesian initials and simplifying those of Chinese initials which are identical to Indonesian initials; third, using the Indonesian alphabet or syllables as a guide to bring out Chinese initials. All of these can be regarded as the main results of this study and can be used as reference for further studies.